Characterization of the temporomandibular joint of the harbour porpoise (Phocoena phocoena) and Risso's dolphin (Grampus griseus). Issue 4 (April 2015) - McDonald, M.; Vapniarsky-Arzi, N.; Verstraete, F.J.M.; Staszyk, C.; Leale, D.M.; Woolard, K.D.; Arzi, B.
Highlights This is a novel study that characterized the TMJ of two odontocete species. The odontocete TMJ is fundamentally different from other mammals. The TMJ disc is composed of collagen fibres, adipose globules, vessels and nerves. The TMJs of odontocetes exhibit a unique structure function relationship.